(3GdfRgI GdSfjI aj CNHGQ Gdedhc GdeUQjIs - (3YHO GdYRjR Hf YeQ Hf eMeO, YR GdOjf , CHh GdNjQ , GdTgjQ HGHf agO,J (B920 (3g` s
(3ChdgG (B:s
(3hHYO agPg fRgI SfjI eeG jWdH ef CNHGQ GdNdaGA hGdedhc GdeUQjI s
(3BNQgG (B:s
(3jfJgi HGdOYGA ddSdGWjf GdYKeGfjjf (B( (3LOO Gddg dge ai cd hbJ fUQkG , hNJe dge HNjQ ai G dOfjG hai GdBNQI , HeMeO hBdg hUMHg CLeYjf , hGdMeO ddg QH GdYGdejf s
(3fSNI NRGFfjI eLOhdIs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1766) s
Keywords: (3GdJGQjNs